1986
DOI: 10.1128/mcb.6.5.1624
|View full text |Cite
|
Sign up to set email alerts
|

Use of a novel S1 nuclease RNA-mapping technique to measure efficiency of transcription termination on polyomavirus DNA.

Abstract: We devised a strategy to measure the efficiency of transcription termination in vivo by RNA polymerase on polyomavirus DNA. Pulse-labeled nuclear RNA was hybridized with a single-stranded polyomavirus DNA fragment which spans the transcription initiation region. Hybrids were treated with RNase, bound to nitrocellulose filters, eluted with S1 nuclease, and analyzed by gel electrophoresis. The ratio of full-length to less-than-full-length DNA-RNA hybrids was used to calculate transcription termination frequency.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…Using this method, it was determined that about 70% of RNA polymerase II molecules terminate each time around the polyoma genome (40). This is in good agreement with the predicted distribution based on direct measurements of late transcription termination using 3H-uridine pulse labeling (43). The RT-PCR assay we use also gives the same quantitative results as RNAse protection assays for leader-leader splicing (data not shown).…”
Section: Introductionsupporting
confidence: 71%
“…Using this method, it was determined that about 70% of RNA polymerase II molecules terminate each time around the polyoma genome (40). This is in good agreement with the predicted distribution based on direct measurements of late transcription termination using 3H-uridine pulse labeling (43). The RT-PCR assay we use also gives the same quantitative results as RNAse protection assays for leader-leader splicing (data not shown).…”
Section: Introductionsupporting
confidence: 71%
“…The late leader is a 57-base exon encoded only once in the viral genome but found in multiple tandem copies on polyoma late mRNAs (26). These repeats are generated by leader-to-leader splicing of giant primary transcripts produced as a result of inefficient termination (27). Recent studies on L-RNA splicing in our laboratory have indicated that before efficient mVP1 splicing is possible, leader-to-leader splicing must occur.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, RNA polymerase II must be designed to transcribe these genes without interruption until the functional end of the gene has been reached. Since this functional end is the site where cleavage and polyadenylation take place, it has occurred to us (and others: Acheson, 1984;Citron et al, 1984;Lanoix et al, 1986;Tseng and Acheson, 1986;Whitelaw and Proudfoot, 1986) that polyadenylation signals may themselves transmit to RNA polymerase II the information required to terminate transcription. Falck-Pedersen et al (1985) showed that insertion of a 1.6-kb fragment of the mouse 3-globin gene, including the polyadenylation signal, within the adenovirus ElA gene caused efficient termination during the early phase of adenovirus infection.…”
Section: Introductionmentioning
confidence: 99%